Use of Nonsteroidal Anti-inflammatory Drugs (NSAIDs) in Amateur Sports – Efficacy and Safety: A Review of Current Literature - Ocicki, Dawid; Nowiński, Igor; Kobryń, Pola; Bojarski, Michał; Kwiatkowski, Michał; Musielak, Michał Fryderyk; Kobryń, Iga; Zybert, Aleksandra; Borowska, Aleksandra; Grabowski, Jakub (Quality in Sport, 2026)
Objective: To evaluate current evidence on the efficacy and safety of nonsteroidal anti-inflammatory drugs (NSAIDs) in amateur athletes, with particular emphasis on pain relief, recovery, performance outcomes, and adverse health effects. Methods: This review synthesised recent literature on NSAID use in physically active populations, with a focus on clinical efficacy, usage patterns, and exercise-related adverse effects. Results: NSAID use in amateur sport is common, frequently self-directed, and often prophylactic. Although these agents may provide modest short-term analgesia, controlled studies do not show consistent benefits for performance, strength recovery, training adaptation, or return to play. Mechanistically, NSAIDs inhibit prostaglandin-mediated pathways involved not only in pain and inflammation, but also in renal perfusion, gastrointestinal mucosal protection, and exercise-related tissue adaptation. During prolonged or high-intensity exercise, particularly in endurance settings characterised by dehydration and heat stress, NSAID exposure may impair renal autoregulation and increase the risk of acute kidney injury. It may also aggravate gastrointestinal mucosal injury and permeability. Cardiovascular risk remains less clearly defined in athletes, but remains clinically relevant, especially in older individuals or those with pre-existing risk factors. Conclusions: NSAIDs should not be used routinely to prevent expected soreness or to support endurance participation. Their clearest role is brief, individualised use for selected acute injuries, in which analgesia must not be mistaken for accelerated healing. For general practitioners, the key recommendation is cautious prescribing at the lowest effective dose for the shortest necessary duration, combined with explicit counselling on renal, gastrointestinal, and cardiovascular risks and consideration of safer alternatives, including topical NSAIDs, paracetamol, load modification, and rehabilitation.